Managed Labor Migration in Afghanistan : Demographic Profile, Short-Term Projections, and Supply of Migration in Afghanistan - Garrote Sanchez, Daniel (World Bank, Washington, DC, 2018)
Afghanistan has one of the youngest populations in Asia, creating strong demographic pressure in the labor market. Around 400,000 youth will continue to enter the labor force annually during the next years. Given the significant slowdown the country’s economic activity, the pace at which jobs are generated is and will be insufficient. Through an analysis of labor supply and demand, thispaper estimates substantial net emigration pressures for the years 2016–2030, on the order of around 200,000 people per year. The projected profile of future migrants is one of young men with some basic level of education and from middle-income households. In addition to this economic migration, other factors like increased insecurity, conflict, and natural disasters might further accentuate these dynamics.